Fuzzy Binary Relation Matrix and Its Application in Medical Diagnosis - D. S. Hooda; Divya Jain (Mathematics and Computer Science: Contemporary Developments Vol. 3, 2024)
In the present chapter, a fuzzy matrix was introduced and different operations on two fuzzy matrices were defined with examples. The lattice of fuzzy matrices was explained and characterized by a theorem. The fuzzy binary relation matrix and its inverse were defined with examples. Its application in a medical diagnosis model was studied and illustrated with an example. Finally, a conclusion and references were provided.